Arranjo de plantas e seus efeitos na produtividade de grãos e teor de óleo em canola - Kruger, Cleusa Adriane Menegassi Bianchi (2011)
The adjustment plant arrangement is one of the fundamental management techniques for canola show positive reaction in the ability to absorb light energy, nutrients and water, which reflects on maximizing the production of photosynthate directed to the plant and grains. The aim of this study was to assess the interference of arrangement plant on direct and indirect components of yield in canola, and includes determining the effects produced in oil content. The study was conducted at the Instituto Regional de Desenvolvimento Rural do Departamento de Estudos Agrários da Universidade Regional do Noroeste do Estado do Rio Grande do Sul (IRDeR/DEAg/UNIJUÍ) in Augusto Pestana, RS, involving the execution of three experiments for different spacing of 0.20, 0.40 and 0.60m. The experimental design consisted of a factorial arrangement in randomized blocks with four replicates of 2 x 2 x 4, for the crop year (2008 and 2009), genotype (Hyola 432 and 61) and plant density (20, 40, 60 and 80 plants m-2) in each set line spacing. Components were determined direct and indirect grain yield, oil content, morphological and adaptive, as well as the thermal and solar radiation during the grain filling. The year of cultivation was more effective in changing the grain yield and other traits in canola direct production and oil content, followed by the genetic potential to grow and smaller share of the planting density. The cv. Hyola 432 shows greater effectiveness in maximizing grain yield over Hyola 61 regardless of year, row spacing and planting density. Moreover, in the shortest space of culture, the character of direct and indirect yield high values of heritability and character number of tertiary branches shows stability when subjected to strong variations in the plants arrangement. The thermal shows no correlation with grain yield and oil content. On the other hand, variables related to the crop cycle are associated with the thermal and solar radiation accumulated in the grain filling stage of canola.